Language Games in Primary Arabic Learning: A Pre-Experimental Study - Irawati; Anshar Zulhelmi (Jurnal Bahasa dan Sastra Pusaka Cendekia, 2026)
This study re-examines classroom language games in primary Arabic instruction at Madrasah Ibtidaiyah Negeri 1 Banda Aceh and evaluates changes in students’ short-term learning achievement. The revised analysis uses a pre-experimental one-group pretest-posttest design supported by classroom observation. The analyzed intervention group comprised 18 students, with achievement measured before and after game-based Arabic learning. Mean scores increased from 28.33 (SD = 11.38) to 72.50 (SD = 11.01), producing a mean gain of 44.17 points; all students improved. Because gain scores showed marginal non-normality, a Wilcoxon signed-rank test was used as the primary inferential analysis and indicated a significant difference (W = 0, p < .001). A paired-samples t test produced the same conclusion, t(17) = 23.16, p < .001. Classroom observations also suggested greater participation and enthusiasm, although motivation was not measured with a validated scale. The findings indicate a strong association between the intervention period and improved achievement, but causal claims remain limited by the absence of a control group, the small sample, and incomplete documentation of the intervention protocol   Penelitian ini menelaah kembali penggunaan permainan bahasa dalam pembelajaran bahasa Arab tingkat dasar di Madrasah Ibtidaiyah Negeri 1 Banda Aceh dan mengevaluasi perubahan hasil belajar jangka pendek peserta didik. Analisis revisi menggunakan desain pra-eksperimental satu kelompok dengan pretest-posttest yang didukung observasi kelas. Kelompok intervensi yang dianalisis berjumlah 18 peserta didik dan hasil belajar diukur sebelum serta sesudah pembelajaran bahasa Arab berbasis permainan. Nilai rata-rata meningkat dari 28,33 (SD = 11,38) menjadi 72,50 (SD = 11,01), dengan kenaikan rata-rata 44,17 poin; seluruh peserta didik mengalami peningkatan. Karena skor selisih menunjukkan penyimpangan marginal dari normalitas, uji Wilcoxon digunakan sebagai analisis inferensial utama dan menunjukkan perbedaan signifikan (W = 0; p < 0,001). Uji t berpasangan memberikan kesimpulan yang sama, t(17) = 23,16; p < 0,001. Observasi kelas juga mengindikasikan partisipasi dan antusiasme yang lebih tinggi, tetapi motivasi tidak diukur menggunakan skala tervalidasi. Temuan menunjukkan hubungan kuat antara periode intervensi dan peningkatan hasil belajar, namun klaim kausal dibatasi oleh ketiadaan kelompok kontrol, ukuran sampel kecil, dan dokumentasi intervensi yang belum lengkap